Ethical Dilemma Do Not Ressuscitation (DNR) in Nursing Practice - Susanti, Aries; Paramitasari, Ketut Citra; Putra, Kadek Andika Dwi; Cintariasih, Putu; Suryani, Ni Wayan; Wulandari, Ida Ayu Putri (Babali Nursing Research, 2024)
Introduction: DNR (Do Not Resuscitate) is a condition where the patient experiences cardiac arrest but chooses not to undergo resuscitation. However, the legal consequences of DNR actions, which may either allow or completely prohibit these actions, can vary in different countries. Nurses frequently encounter ethical dilemmas resulting from DNR situations. This literature review explored nurses' ethical dilemmas regarding DNR and strategies to overcome them.Methods: This literature review examined previous research findings published in articles. Article searches were conducted using PubMed, ScienceDirect, and Google Scholar, employing keywords such as "DNR," "Nursing Ethics," and "Ethical dilemma," as well as combinations thereof like "DNR in a nursing ethical dilemma." Fifteen articles meeting the inclusion criteria were selected.Results: Making DNR decisions for patients significantly impacted the continuity of patient care in hospitals. These decisions were influenced by religion/beliefs, life expectancy, limited resources, and past experiences. Nurses stressed the importance of discussing DNR situations openly. Moreover, nurses were crucial in addressing misunderstandings surrounding patient care with DNR orders through practice, education, advocacy, policy implementation, and research.Conclusion: Nurses require adequate training and education in end-of-life ethics and DNR decision-making to prevent detrimental actions and ensure patients' peaceful, dignified terminal care.